Nanomaterials for plant growth - Goh, Shermaine Shi Min (Nanyang Technological University, 2020)
Upconversion nanoparticles (UCNP) have been studied only in recent years for ap-plication in various fields such as optoelectronic, bioimaging and bioscience. The effects of varying pH and holding times, on the size, length and phases of UCNP were studied in this work by using either pure lauric acid (LA), pure citric acid (Cit) or Cit-LA cosurfactant system at molar ratios of 4:1. Then, the produced UCNP with the optimum conditions would be used for further applications in plants, through the roots and leaves. The particles were prepared using hydrothermal autoclave synthe-sis. The surfactant ratio, reaction time and pH were investigated and optimized for desired size, shape and phase of the UCNP, and further characterized by using SEM, XRD and EDX, for this application. This study showed that differences in ligand properties, especially chelating abilities is essential in determining the particle size, shape and phase transformation. SEM images showed that out of all the experimental variations worked on, an optimal hydrothermal reaction conditions to pro-duce a mixture of hexagonal and cubic phases a & b -NaYF4:Yb,Tm with optimal av-erage diameter of 23 nm and average length of 92 nm have been determined: the re-action was done using Cit-LA cosurfactants at 4:1 molar ratio, at pH 7 and for 6 h. XRD showed that in general, for Cit-LA and LA, synthesized UCNP had both a & b phases. On the other hand, using pure Cit surfactant produced significantly larger, predominantly b phase UCNP.